Lead concentrations in human plasma, urine and whole blood - Bergdahl, Ingvar A.; Schütz, Andrejs; Gerhardsson, Lars; Jensen, A.; Skerfving, Staffan (Scandinavian Journal of Work, Environment & Health, 1997)
' ' OBJECTIVES ': 'Blood-lead levels (B-Pb), and to some extent urinary lead (U-Pb), are the most employed measures of lead exposure and risk. However, the small fraction of lead present in plasma (usually below 1% of that in blood) is probably more relevant to lead exposure and toxicity. Nevertheless, the lead content of plasma lead (P-Pb) has only seldom been used, mainly due to analytical limitations, which have now been overcome. We examined P-Pb in occupationally exposed subjects, as well as its relationship with B-Pb and U-Pb. ' ' METHODS ': 'Blood samples were obtained from 145 male workers, 110 of whom were employed in lead work. After a simple dilution of plasma, P-Pb was determined by inductively coupled plasma mass spectrometry. The detection limit was 0.04 µg/l, and the imprecision was 5%. ' ' RESULTS ': 'The lead concentration ranges were 0.20–37 µg/l for P-Pb, 0.9–176 µg/l (density adjusted) for U-Pb, and 9–930 µg/l for B-Pb. A close exponential relation was obtained between B-Pb and P-Pb. When B-Pb was plotted versus log P-Pb, a straight line (log P-Pb=0.00225 · B-Pb – 0.58; r=0.97) was obtained. Both the relation between U-Pb and P-Pb and that between U-Pb and B-Pb showed a large scattering (r=0.78 in both cases). The relation to B-Pb appeared to be exponential, while that to P-Pb appeared to be linear. ' ' CONCLUSION ': 'The low detection limit and good precision of P-Pb determinations make it possible to use P-Pb in assessments of lead exposure and risk. Furthermore, in relative terms, P-Pb is a more sensitive measure than B-Pb, especially at high lead levels. This development is of importance for studies of exposure, possibly also for studies of risks.
Keywords: biological monitoring; inductively coupled plasma mass spectrometry; serum